Knowledge and Attitudes of the Faculty of Theology Students on Organ Transplantation - Yilmaz, Seher Gürdil (Journal of religion and health, 2017)
The objective in this study is to determine the knowledge and attitudes of the Faculty of Theology students on organ transplantation. The study that was planned as a descriptive study took place between March-May 2014 with the participation of 119 students enrolled at the Faculty of Theology. It was determined as a result of the study that the students see lack of knowledge (49.6%) as the top obstacle for organ transplantation followed by religion (21%), that 52.1% accept that organ transplantation is not forbidden in Islam; that 27.7% agree with the thought that considers it disturbing and unnerving to carry an organ or tissue from another body; that 80.7% agree with the idea stating that organ transplantation should be carried out even if it provides only a possibility for treatment or for prolonging one’s life and that 82.4% agree with the opinion that statements in favor of organ transplantation to be declared by the Directorate of Religious Affairs will increase organ transplantation. Clergymen play an important role in affecting the behavior and attitudes of large public masses, and thus it is important that the positive ideas of these individuals with regard to organ donation will thus have indirect but positive effects on the attitudes of the public with regard to organ transplantation. Hence, it is thought that determining the attitudes of clergymen candidates who will educate the public both at schools and at places of prayer and increasing their awareness in this subject will contribute to increasing the awareness of the public with regard to organ donation.